Host cell proteins interacting with the 3' end of TGEV coronavirus genome influence virus replication. - Galán, C; Sola, I; Nogales, A; Thomas, B; Akoulitchev, A; Enjuanes, L; Almazán, F (2009)
Coronavirus RNA synthesis is performed by a multienzymatic replicase complex together with cellular factors. This process requires the specific recognition of RNA cis-acting signals located at the ends of the viral genome. To identify cellular proteins involved in coronavirus RNA synthesis, transmissible gastroenteritis coronavirus (TGEV) genome ends, harboring essential cis-acting signals for replication, were used as baits for RNA affinity protein purification. Ten proteins were preferentially pulled down with either the 5' or 3' ends of the genome and identified by proteomic analysis. Nine of them, including members of the heterogeneous ribonucleoprotein family of proteins (hnRNPs), the poly(A)-binding protein (PABP), the p100 transcriptional co-activator protein and two aminoacyl-tRNA synthetases, showed a preferential binding to the 3' end of the genome, whereas only the polypyrimidine tract-binding protein (PTB) was preferentially pulled down with the 5' end of the genome. The potential function of the 3' end-interacting proteins in virus replication was studied by analyzing the effect of their silencing using a TGEV-derived replicon and the infectious virus. Gene silencing of PABP, hnRNP Q, and glutamyl-prolyl-tRNA synthetase (EPRS) caused a significant 2 to 3-fold reduction of viral RNA synthesis. Interestingly, the silencing of glyceraldehyde 3-phosphate dehydrogenase (GAPDH), initially used as a control gene, caused a 2 to 3-fold increase in viral RNA synthesis in both systems. These data suggest that PABP, hnRNP Q, and EPRS play a positive role in virus infection that could be mediated through their interaction with the viral 3' end, and that GAPDH has a negative effect on viral infection.